2009
DOI: 10.1111/j.1439-0531.2009.01379.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effect of the Aromatase Inhibitor, Anastrazole, to the Antioestrogen, Tamoxifen Citrate, on Canine Prostate and Semen

Abstract: This study compared the efficiency of the aromatase inhibitor, anastrazole, with the antioestrogenic receptor blocker, tamoxifen, on normal (NRL) and hyperplastic prostate glands. Forty healthy dogs were classified as NRL (n = 18) or abnormal (ABN) with benign prostate hyperplasia (n = 22). The dogs were randomly assigned to one of the following six groups, treated for 60 days; oral placebo for normal (NRL-PLC; n = 6) and abnormal (ABN-PLC; n = 6), oral anastrazole 0.25-1 mg/day, for normal (NRL-ANZ, n = 6) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…In a study of seven beagles with spontaneous BPH, treatment with the SERM Tamoxifen resulted in decreased prostate volume [165]. A randomized trial of Tamoxifen in dogs with BPH showed an average 28.5% decrease in prostate volume compared to placebo [198]. SERMs are well-tolerated in men, and have been shown to ameliorate side effects of androgen ablation therapy in men with metastatic prostate cancer, reduce fracture risk and improve lipid profiles [199, 200].…”
Section: Future Challenges and Directionsmentioning
confidence: 99%
“…In a study of seven beagles with spontaneous BPH, treatment with the SERM Tamoxifen resulted in decreased prostate volume [165]. A randomized trial of Tamoxifen in dogs with BPH showed an average 28.5% decrease in prostate volume compared to placebo [198]. SERMs are well-tolerated in men, and have been shown to ameliorate side effects of androgen ablation therapy in men with metastatic prostate cancer, reduce fracture risk and improve lipid profiles [199, 200].…”
Section: Future Challenges and Directionsmentioning
confidence: 99%
“…In another study, tamoxifen was administered for 60 days (2.5–10 mg/day) to 6 dogs with normal prostate glands and 8 dogs presenting BPH (Gonzalez et al. ). At the end of the treatment, the prostatic volume had decreased by 28.5 ± 4.3% in BPH males.…”
Section: Treatment For Bphmentioning
confidence: 99%
“…No clinical or haematological side effects were observed during 4 weeks of post-treatment follow-up (Corrada et al 2004). In another study, tamoxifen was administered for 60 days (2.5-10 mg/day) to 6 dogs with normal prostate glands and 8 dogs presenting BPH (Gonzalez et al 2009). At the end of the treatment, the prostatic volume had decreased by 28.5 AE 4.3% in BPH males.…”
Section: Antioestrogensmentioning
confidence: 99%
See 2 more Smart Citations